Investment Gaps in Latin America and the Caribbean - Francesca Castellani; Marcelo Olarreaga; Ugo Panizza; Yue Zhou (Revue Internationale de Politique de Développement)
We estimate public investment gaps in a sample of developing countries using a public investment demand function. We then use gross domestic product (GDP) per capita projections, forecasts of structural transformation, and three Sustainable Development Goals (SDGs) targets (poverty, infant mortality and lower secondary school completion) to predict public investment needs in 2030 in Latin American and Caribbean countries. Our estimates suggest that in 2015 their total public investment gap was close to USD 170 billion (3.1 per cent of the region’s GDP) and expected to surpass USD 1.4 trillion (12.4 per cent of the region’s GDP) by 2030 if the SDGs were to be reached.